Pure Relationality as a Sociological Theory of Communication - Whimster, Sam (Frontiers in Sociology, 2018)
In order to explain the success of populist politicians use of social media, we need to subtract the social from relationality and separate social relationships from network theory applications. A pure theory of relationality is suggested by Werner Heisenberg's breakthrough in quantum mechanics. It is argued that sociology, to its detriment, has failed to incorporate a theory of communication, one adequate to the explosion of social media and the recent rise of populist politics, here instanced by Donald Trump. Realizing the underlying importance of communication technology in all social relationships, and treating these two aspects in a complementary fashion, is the purpose of this essay in sociological theory.